The Responsibility of Community Sustainability from the Frontlines of Climate Change - Pratt, Nastassia (International Journal of Bahamian Studies, 2021)
Bahamian communities are vulnerably positioned on the frontlines of climate change due to global warming. Small Island Developing States (SIDS) in the Global South, including The Bahamas, have been identified as especially vulnerable to the impacts of climate change due to their unique characteristics. There is now a pressing need for sustainable community development that involves a cross-disciplinary, climate change adaptation approach that promotes resilience strengthening. This type of planning strategy was needed in the preparation and implementation of emergency shelters before the passing of Hurricane Dorian and in the ongoing rebuilding efforts of communities post-Dorian. Further, the way in which key stakeholders engage with these activities has implications on The Bahamas’ capacity for climate change resilience. This paper will identify gaps in adaptation processes within Dorian-hit redevelopment and the national system of sheltering and evacuation. It goes on to argue the need for social equity in planning for the protection of vulnerable communities, inclusive of informal settlements like those destroyed by Hurricane Dorian in North Abaco. Lastly, this paper will make recommendations toward Bahamian climate change resilience.